Interval and Point Direction Finding of Radio Emission Sources for Broadband Radio Monitoring - M. E. Shevchenko (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. The point and interval direction finding of radio sources is used for broadband radio monitoring in the frequency domain. The initial data for broadband radio monitoring are spectral samples obtained from an M-element antenna array by multichannel reception. Point direction finding is based on a grouping of point estimates of azimuth and elevation angle formed for each frequency sample, in which signal components are detected. A single estimate of azimuth and elevation angle is made based on the grouped point estimates in the range of neighbouring frequency samples. Interval direction finding is based on the azimuth and elevation estimates formed entirely from the interval of adjacent frequency samples, in which the signal components are found, and the subsequent refinement of frequency sample interval boundaries for each radio source in multisignal mode by spatial selection methods. Point direction finding is mainly implemented in single-signal mode in modern operating broadband radio monitoring complexes, while the multi-signal mode based on MUSIC or ESPRIT is implemented in the time domain in a narrow frequency band.Aim. Development and investigation of methods for point and interval direction finding in multi-signal mode, as well as development of recommendations for their practical application in multi-signal and single-signal modes.Methods. Multi-signal mode for point and interval direction finding was implemented using MUSIC and ESPRIT. An experimental study of the developed direction finding methods in single-signal and multi-signal (on ESPRIT) modes with overlapping signal spectra was carried out by processing the recorded real signals. The records were made using a seven-channel coherent synchronous receiver connected to a seven-element 60° angle antenna array.Results. The research results are presented by frequency-azimuth panoramas and estimates of the amplitude spectra of separated signals and direction finding accuracy indicators.Conclusion. It was experimentally demonstrated that point direction finding should be used in single-signal mode provided the absence of information on the number of signals in the observed data. Interval direction finding is recom-mended in multi-signal mode for improving the accuracy and real-time feasibility of the process.